A novel approach to risk assessment for occupational health and safety using Pythagorean fuzzy AHP & fuzzy inference system. (March 2018) - Ilbahar, Esra; Karaşan, Ali; Cebi, Selcuk; Kahraman, Cengiz
Highlights: PFPRA and PFFMEA approaches are firstly proposed to literature in this paper. PFPRA is based on the integration of Fine Kinney, Pythagorean fuzzy AHP, and FIS. PFFMEA is based on the integration of FMEA, Pythagorean fuzzy AHP, and FIS. The methods are applied on the risks of an excavation process in a construction yard. These methods present a more accurate risk assessment for occupational safety. Abstract: Occupational health and safety involves systematic studies aimed at protecting employees from harmful conditions that might be caused by various reasons during the execution of work in the workplace. Different from the literature, in this study, a novel integrated approach, Pythagorean Fuzzy Proportional Risk Assessment (PFPRA), including Fine Kinney, Pythagorean fuzzy analytic hierarchy process, and a fuzzy inference system is used for risk assessment in the field of occupational health and safety. The main difference of the proposed approach is the integration of these methods in a way providing a more accurate risk assessment. The risks of an excavation process in a construction yard are assessed by the proposed method. The results are compared with Pythagorean Fuzzy Failure Modes and Effects Analysis (PFFMEA) and it is revealed that the proposed method produces reliable and informative outcomes better representing the vagueness of decision making process.